Design and Evaluation of Nuclear System for ARIES-ACT2 Power Plant with DCLL Blanket. (4th July 2017) - El-Guebaly, L.; Mynsberge, L.; Davis, A.; D'Angelo, C.; Rowcliffe, A.; Pint, B.; ,
Abstract: The ARIES team has examined a multitude of fusion concepts over a period of 25 years. In recent years, the team wrapped up the Advanced Research, Innovation, and Evaluation Study (ARIES) series by completing the detailed design of the ARIES–Advanced and Conservative Tokamak (ARIES-ACT2) power plant—a plant with conservative physics and technology, representing a tokamak with reduced-activation ferritic/martensitic (RAFM) structure and dual-coolant lead-lithium blanket. The integration of nuclear assessments (neutronics, shielding, and activation) is an essential element to ARIES-ACT2 success. This paper highlights the design philosophy of in-vessel components and characterizes several nuclear-related issues that have been addressed during the course of the study to improve the ARIES-ACT2 design: sufficient breeding of tritium to fuel the plasma, well-optimized in-vessel components that satisfy all design requirements and guarantee the shielding functionality of its radial/vertical builds, survivability of low-activation/radiation-resistant structural materials in 14-MeV neutron environment, activation concerns for RAFM and corrosion-resistant oxide-dispersion-strengthened alloys, and an integral approach to handle the mildly radioactive materials during operation and after decommissioning.